A) x=-2 y= 1 B) x= -1 y= -2 C) x=1 y=2 D) x= -2 y= -1 E) x=2 y= 2
A) x=1 y=2 B) x=3 y=3 C) x= -1 y=1 D) x=-1 y=-2 E) x=-2 y= 1
A) x=-3 y=-1 B) x=4 y=1 C) x=4 y=2 D) x=2 y= 1 E) x=-2 y=1
A) x= -1 y= -2 B) x= 5 y= 6 C) x=1 y=2 D) x=2 y= -5 E) x=4 y=1
A) x=-2 y= 1 B) x=3 y=1 C) x=-3 y=-1 D) x=-2 y= 1 E) x=1 y=2
A) x=1 y=2 B) x=2 y= 1 C) x=4 y=2 D) x=-3 y=-1 E) x=3 y=1
A) x=-2 y= 1 B) x=1 y=2 C) x=4 y=2 D) x= -1 y= -2 E) x=-1 y=1
A) x=2 y=1 B) x=5 y=3 C) x=-1 y= -1 D) x=3 y=3 E) x=4 y=2
A) x= 2 y= 3 B) x=-3 y=-1 C) x=4 y=1 D) x=-2 y= 1 E) x=1 y=2
A) x= -3 y= 2 B) x=2 y= 1 C) x=2 y= -5 D) x= 2 y= 3 E) x=-3 y=-1 |